Aluminium-vacancy complexx in Ge₁₋ₓCₓ - Chroneos, A.I.; Goulatis, I.L. (Functional Materials, 2007)
A brief review on the potential importance of Ge₁₋ₓCₓ for electro-optic applications and ab initio calculations of the aluminium-vacancy complexes are presented. The stability and geometry of aluminium-vacancy complexes has been examined within the frame of density functional theory and the use of the pseudopotential plane-wave method. The predictions highlight the preference of the cluster geometry on the energetics in Ge₁₋ₓCₓ and the effect of carbon concentration on the stability of clusters.